2019
DOI: 10.4274/tjod.galenos.2019.21384
|View full text |Cite
|
Sign up to set email alerts
|

Fetal nuchal translucency: is there an association with birthweight and neonatal wellbeing?

Abstract: Objective: To evaluate the relationship between nuchal translucency (NT) values with birthweight and the wellbeing of the newborn. Materials and Methods: This retrospective cohort study that included 508 patients made use of data on healthy full-term, singleton, live birth newborns in a university hospital between 2016 and 2018. The relationship between the NT multiple of the median (MoM) value and maternal body mass index, birthweight, sex, need for neonatal intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(38 reference statements)
0
2
1
Order By: Relevance
“…Hackmon et al's study in 2017 showed a correlation between birth weight and early fetal measurements such as biparietal diameter (BPD) and crown-rump length (CRL), NT measurements, and NT percentiles (11). There is a predominant opinion in the literature that a correlation exists between LGA and NT measurements (2,10,13,27,30,31), but our study revealed no correlation between NT measurements and non-LGA AGA and SGA groups. Therefore, our data show that NT measurements within normal limits can be useful parameters for detecting future macrosomic or LGA fetuses.…”
Section: Discussioncontrasting
confidence: 66%
“…Hackmon et al's study in 2017 showed a correlation between birth weight and early fetal measurements such as biparietal diameter (BPD) and crown-rump length (CRL), NT measurements, and NT percentiles (11). There is a predominant opinion in the literature that a correlation exists between LGA and NT measurements (2,10,13,27,30,31), but our study revealed no correlation between NT measurements and non-LGA AGA and SGA groups. Therefore, our data show that NT measurements within normal limits can be useful parameters for detecting future macrosomic or LGA fetuses.…”
Section: Discussioncontrasting
confidence: 66%
“…[3] Fetuses with increased NT are at high risk for chromosomal, structural, and genetic anomalies, and generally, it is accepted as a non-specific sign of fetal abnormality. [6,7] For this reason, abnormal results detected in NT values may affect the weight of the fetus or may help us to predict other adverse outcomes. Therefore, according to the literature, ultrasound markers and biochemical markers used in the first-trimester screening test are not only used in aneuploidy risk calculation but have also been shown to predict adverse pregnancy outcomes since the first trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, according to the literature, ultrasound markers and biochemical markers used in the first-trimester screening test are not only used in aneuploidy risk calculation but have also been shown to predict adverse pregnancy outcomes since the first trimester of pregnancy. [6] The aim of this study was to investigate the relationship between NT values measured in the first trimester and maternal serum free β-hCG and PAPP-A levels with term birth weight and well-being of the newborn.…”
Section: Introductionmentioning
confidence: 99%